Toán 8

Do Thi Thu Huong

Học sinh tiến bộ
Thành viên
2 Tháng ba 2017
227
66
154

Kiều Đặng Minh Ngọc

Học sinh
Thành viên
23 Tháng năm 2017
230
67
36
20
Nhà !!
mail.google.com
Cho S = ( [tex]\frac{x}{x^2 - 36}[/tex] - [tex]\frac{x - 6 }{x^2 + 6x}[/tex] ) : [tex]\frac{2x - 6}{x^2 + 6x}[/tex] +
[tex]\frac{x}{6 - x}[/tex]


a/ Rút gọn S
b/ Tìm x để giá trị của S = -1
ĐKXĐ : [tex]x\neq 3 ; x\neq \pm 6[/tex]
a, Khi đó ta có : S =[tex](\frac{x}{(x-6)(x+6)}-\frac{x-6}{x(x+6)}).\frac{x(x+6)}{2(x-3)}+\frac{x}{6-x}[/tex]
S =[tex]\frac{x^{2}-(x-6)^{2}}{x(x-6)(x+6)}.\frac{x(x+6)}{2(x-3)}-\frac{x}{x-6}[/tex]
S =[tex]\frac{x^{2}-x^{2}+12x-36}{2(x-6)(x-3)}-\frac{x}{x-6}[/tex]
S =[tex]\frac{12(x-3)}{2(x-6)(x-3)}-\frac{x}{x-6}[/tex]
S = [tex]\frac{6}{x-6}-\frac{x}{x-6}[/tex]
S =[tex]\frac{6-x}{x-6}[/tex]
S = -1
b,Với mọi [tex]x\neq 3 ; x\neq \pm 6[/tex] thì S = -1
 
  • Like
Reactions: Do Thi Thu Huong
Top Bottom